Há associação entre características sociodemográficas, complicações, depressão, adesão medicamentosa e qualidade de vida em hemodiálise? Is there association between sociodemographic characteristics, complications, depression, medications adherence and life quality in hemodialysis? - Pretto, Carolina Renz; Stumm, Eniva Miladi Fernandes (Revista Enfermagem Atual In Derme, 2019)
Objetivo: avaliar associação entre características sociodemográficas, complicações decorrentes da doença renal crônica, hemodiálise, adesão à terapêutica e indicativos de depressão com dimensões da qualidade de vida relacionadas à saúde em pacientes com insuficiência renal submetidos ao tratamento hemodialítico. Método: pesquisa transversal, com 183 pacientes das unidades renais região Noroeste e Missões, Rio Grande do Sul. Utilizou-se questionário sociodemográfico e clínico, Kidney Disease and Quality of Life Short-Form, Inventário de Depressão de Beck e Teste de Morisky-Green. A análise ocorrerá com estatística descritiva, analítica e inferencial. Respeitados preceitos éticos de pesquisa com pessoas. Resultados Esperados: identificar associação entre características individuais, complicações, adesão à terapêutica e depressão com escores diminuídos de qualidade de vida e mobilizar a assistência multiprofissional direcionada a esses aspectos e determinantes para promover vida de qualidade a essa população. Palavras-chave: Doença Renal Crônica; Depressão; Qualidade de Vida; Enfermagem; Adesão à Medicação. ABSTRACT Objective: to evaluate the association between sociodemographic characteristics, complications resulting from chronic kidney disease, hemodialysis, adherence to therapy and indicative of depression with health-related quality of life dimensions in patients with renal failure undergoing hemodialysis treatment. Method: cross-sectional study, with 183 patients from the kidney care units of the Northwest region and Missões, Rio Grande do Sul, Brazil. A sociodemographic and clinical questionnaire was used, Kidney Disease and Quality of Life Short-Form, Beck Depression Inventory and Morisky-Green Test. The analysis will take place with descriptive, analytical and inferential statistics. Respectful ethical precepts of research with people. Expected Results: identify association between individual characteristics, complications, adherence to therapy and depression with diminished quality of life scores and mobilize multiprofessional care directed to these aspects and determinants to promote quality life for this population. Keywords: Chronic Renal Insufficiency; Depression; Quality of Life; Nursing; Medication Adherence.